Highly efficient adsorption behavior and mechanism of Urea-Fe3O4@LDH for triphenyl phosphate. (December 2020) - Hao, Mengjie; Gao, Pan; Yang, Dian; Chen, Xuanjin; Xiao, Feng; Yang, Shaoxia
Abstract: The emergence of organophosphorus flame retardants and the efficient removal from aquatic environments have aroused increasing concerns. The Urea functionalized Fe3 O4 @LDH (Urea-Fe3 O4 @LDH) was prepared and used to adsorb triphenyl phosphate (tphp) for the first time. The tphp adsorption capacity was up to 589 mg g −1, and the adsorption rate reached 49.9 mg g −1 min −1 . Moreover, the influences of various environmental factors (pH, ionic strength and organic matter) on the tphp adsorption on the Urea-Fe3 O4 @LDH were investigated. The initial pH of the solution significantly affected the tphp adsorption, whereas the ionic strength and HA slightly affected the adsorption. The main adsorption mechanism was attributed to electrostatic interaction and π-π interaction. We believe that urea is one of excellent functional groups for the tphp adsorption removal and the materials with urea groups as the adsorbents exhibit good prospects in the future. Graphical abstract: Image 1 Highlights: At the first time, the Urea functionalized Fe3 O4 @LDH was used for the tphp removal. The Urea-Fe3 O4 @LDH exhibited the high TPhP adsorption removal and good cycles. The tphp adsorption capacity of the Urea-Fe3 O4 @LDH was up to 589 mg g −1 . Ionic strength had little effect on the TPhP adsorption on the Urea-Fe3 O4 @LDH.